Social responsibility of a municipal enterprise - Tetłak, Zbigniew (Scientific Journal of Bielsko-Biala School of Finance and Law, 2023)
— <!– [if gte mso 11]> <![endif]–>CSR (Corporate Social Responsibility) is a concept that fundamentally changes the approach to relations with stakeholders, and it is not about strictly business relations. It is also not about obligations or some kind of compensation for the negative effects of the company’s business activity. The essence of this concept is the requirement to understand that the company has not only obligations towards its owners, but also towards society. The idea of corporate social responsibility corresponds in a model way to the mission and objectives of a municipal enterprise performing tasks of a public utility nature, because theoretically there is no conflict of interests between the owners and its clients. Therefore, an important research problem is the search for an answer to the question: Who benefits the most from the activities of a municipal enterprise? Are they members of the local government community (residents) who are the actual owners of the municipal enterprise. <!– [if gte mso 11]> <![endif]–>